Chemoselective Transfer Hydrogenation over MgO as the Catalyst: Acetylnaphthalenes, Diacylbenzenes, Acetophenone, Benzaldehyde, and Various Aliphatic Ketones as Hydrogen Acceptors - Marek Gliński; Olga Dubinin; Klaudia Rostek; Patrycja Waniek (Reactions)
Liquid and vapor phase transfer hydrogenation with 2-alkanols as hydrogen donors in the presence of MgO as a catalyst was studied. A series of dicarbonyl compounds as well as the equimolar mixtures of various monocarbonyl compounds were used as hydrogen acceptors in order to determine the chemoselectivity (ChS) in the reduction of their carbonyl groups. Thus, 1,4-diacetylbenzene was reduced to 1-(4-acetylphenyl)-1-ethanol with 89% ChS and 1,3-diacetyl-4,6-dimethylbenzene with 100% ChS. Mesitylene diacyl derivatives were unreactive in the studied reaction. CTH of an equimolar mixture of benzaldehyde and acetophenone gave benzyl alcohol and 1-PhEtOH with yields of 91 and 3%, respectively (97% ChS). An equimolar mixture of acetophenone and 6-undecanone underwent CTH with yields of the corresponding alcohols of 89 and 2%, respectively, with 98% ChS towards 1-PhEtOH. Significant differences in reactivity in CTH were reported for an equimolar mixture of regioisomeric 1- and 2-acetylnaphthalenes. The yields of the corresponding alcohols were 20 and 68% with a ChS of 77% towards 2-NphCH(OH)Me. In the case of CTH of 3-oxo-2,2-dimethylbutanal and 2,4-bis(spirocyclohexyl)-1,3-cyclobutanedione with 2-propanol, only the solvolysis of the substrates was observed. The products were methyl isopropyl ketone and isopropyl formate for the former diketone and 1-(cyclohexylcarbonyl)-1-(carboisopropoxy)cyclohexane for the latter.